Kinerja Elektroda Platina Terlapis Enzim Butirilkholinesterase-Selulosa Asetat-Glutaraldehida untuk Deteksi Diazinon: Performance of Platina Electrode Coated by Butyrylcholinesterase-Cellulose Acetate-Glutaraldehyde for Diazinon Detection - Thamrin Azis; Nurhaeni; Caterina Bijang; A. Nurwahida (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2020)
Diazinon (o, o-diethyl-o [2-isopropyl-6-methyl pyrimidynyl] phosphorotioate) is one of the organophosphate group pesticides widely used to protect cabbage plants (Brassica olarecea). Pesticide residues left in plants can bind to the cholinesterase enzyme and cause system disruption nerve. Analysis of diazinon residues in cabbage plants needs to be done to determine the level of toxicity caused. The electrochemical biosensor method as an electrochemical sensor uses a working electrode of platinum wire coated with the enzyme butybholchesteresterase (BChE) and cellulose acetate (SA) membrane and glutaraldehyde (GA) can be used for the analysis of pesticide residues. The test results of the SA electrode composition of the 10% GA 20% membrane obtained Nernst factor prices 28.1 µV / decade with a measurement range of 10-9 - 10-6 M, detection limit value of 1.29 x 10-7 M response time of 30 - 300 seconds. Keywords: biosensor, butylochholesterase, membrane, electrochemistry